Nasogastric tube drainage and pyloric intervention after oesophageal resection: UK practice variation and effect on outcomes. Issue 5 (May 2022) - Bull, Alexander; Pucher, Philip H.; Maynard, Nick; Underwood, Tim J.; Lagergren, Jesper; Gossage, James A.; ,
Abstract: Background: Over 1500 patients with oesophageal cancer undergo a resection in the UK each year. At surgery, patients commonly have a nasogastric tube (NGT) placed and may undergo a pyloric intervention. There is conflicting evidence on the use of both NGTs and pyloric interventions during oesophageal resections. We performed a national survey of oesophageal centres and assessed practice variation. Material and methods: An electronic survey was distributed to all resection centres in England, Wales and Scotland. Variations in practice regarding NGTs and pyloric intervention were assessed, and compared to nationally reported centre volumes and length-of-stay data. Results: Most centres (31/39, 79%) responded to the survey. All centres reported routine NGT use. The majority of centres (19/31, 61%) did not perform pyloric interventions. When used, surgical pyloroplasty was the most frequent strategy (8/31, 26%). Routine post-operative radiological assessment was utilised in 9/31 (29%) of centres. Criteria for NGT removal and dietary progression was highly variable, with every centre reporting different protocols. There were no significant differences in practice between high and low volume centres. There were also no trends seen when comparing centres above vs at-or-below the median length-of-stay. The majority (68%) of centres were willing to take part in a trial assessing NGT use and pyloric interventions. Conclusions: Pyloric intervention use varies widely, with no clear link to outcomes. NGT use remains standard practice despite evidence for safe omission. Surgeons require and recognise the need for a trial to assess requirement for NGTs and pyloric intervention after oesophageal resection.